Employee behaviours affecting job satisfaction. (8th August 2019) - Veri, Jhon; Ridwan, Muhammad; Lasman, Feri
This research aims to prove the direct influence of employee behaviour on job satisfaction. An empirical descriptive study was performed, with the sample consisting of 78 employees working in companies processing rubber raw materials in Indonesia. The data were analysed using partial least square method of structural equation modelling. Results reveal that self-efficacy exerts the most influence on job satisfaction. The indicators of this particular employee behaviour are morale and perseverance. Companies should establish good relationships with employees to improve job satisfaction. Enabling it to compete to face globalisation.